Regulation of hypnosis using PID control - Wong, Song Jau. (2010)
Anesthesia implies maintaining a triad of hypnosis, analgesia, and neuromuscular blockade by infusing several drugs which specifically act on each of the above aspects. The hypnosis dynamics of patient can be modeled using a sixth-order nonlinear pharmacokinetic (PK)-pharmacodynamic (PD) model. Control systems are desired for maintaining the hypnosis level to reduce cost and risks. However, due to the nonlinear nature of PD, the responses obtained from these PD models may be slow. This work focuses on examining the feasibility of substituting the nonlinearity of pharmacodynamic models using variable transformation for controlling BIS signal. The closed loop control strategies of four different PID controller arrangements were compared for both PD models with and without variable transformation. Robust performance of the four controllers is tested for a broad range of patients by considering variability in PK-PD parameters. The relative performance of the four controllers is studied for different setpoints, noise, and disturbances in BIS signal. It was found that for PI and PID controller, variable-transformed PD models perform better than nonlinear models.